2018
DOI: 10.4158/ep-2018-0036
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Co-Administration of Sitagliptin With Metformin in Patients With Type 2 Diabetes at Hospital Discharge

Abstract: BG = blood glucose; DPP-4 = dipeptidyl peptidase-4; eGFR = estimated glomerular filtration rate; HbA1c = hemoglobin A1c; T2D = type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 20 publications
(28 reference statements)
2
20
1
Order By: Relevance
“…Several observational and randomized controlled trials have shown that this is an effective regimen in achieving glycemic control and in reducing hospital complications (9,15). However, the requirement of multiple insulin injections and associated risk of hypoglycemia (16,17) has triggered the study of alternative approaches for the management of patients with diabetes in the hospital (18,19) and after discharge (20).…”
mentioning
confidence: 99%
“…Several observational and randomized controlled trials have shown that this is an effective regimen in achieving glycemic control and in reducing hospital complications (9,15). However, the requirement of multiple insulin injections and associated risk of hypoglycemia (16,17) has triggered the study of alternative approaches for the management of patients with diabetes in the hospital (18,19) and after discharge (20).…”
mentioning
confidence: 99%
“…This probably reflects a need to redefine these conditions, in order to minimize unnecessary avoidance of the drug [15]. Even if metformin administration is stopped during admission, it can be safely restarted in most cases a few days prior to discharge, thus facilitating dose adjustment of basal insulin and the building of a discharge regimen [23]. Still, there are significant barriers to its administration to inpatients, including the risk of gastrointestinal adverse effects and lactic acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Gianchandani et al . [23] conducted a multicentre, prospective, non‐randomized, open‐label clinical trial to evaluate the safety and efficacy of combined therapy with metformin and sitagliptin, either with or without basal insulin, in people with type 2 diabetes discharged from general medicine and surgical wards. According to admission HbA 1c concentrations, 253 participants were randomized to three arms: discharged on sitagliptin and metformin [HbA 1c < 53 mmol/mol (7%)]; discharged on sitagliptin, metformin and glargine U100 insulin at 50% of the hospital daily dose [HbA 1c 53–75 mmol/mol (7–9%)]; and discharged on sitagliptin, metformin and glargine U100 insulin at 80% of the hospital daily dose [HbA 1c > 75 mmol/mol (9%)].…”
Section: Methodsmentioning
confidence: 99%
“…An HbA1c‐based diabetes discharge treatment algorithm suggested that resuming outpatient treatment if HbA1c was below 7%, adding basal insulin at 50% to 80% of the dose used in hospital for HbA1c between 7% and 9%, and either basal‐bolus or resumption of outpatient treatment along with basal insulin glargine for HbA1c exceeding 9%, although in a study of this approach nearly half of those discharged on basal‐bolus insulin developed hypoglycemia . The use of a dipeptidyl peptidase (DPP)‐4 inhibitor with a similar regimen appeared to lead to less hypoglycemia . Avoiding rehospitalization is crucial.…”
mentioning
confidence: 99%
“…19 The use of a dipeptidyl peptidase (DPP)-4 inhibitor with a similar regimen appeared to lead to less hypoglycemia. 20 Avoiding rehospitalization is crucial. Rubin observed that as many as one-fifth of patients are readmitted within 30 days of discharge, at a total cost of US $123 billion/year.…”
mentioning
confidence: 99%